Tanggung Jawab Notaris Terhadap Keberadaan Klausula Eksonerasi Dalam Perjanjian Kredit Pemilikan Rumah - Ilham Yulian; Widiya N. Rosari; Ganefi Ganefi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Mortgage Loan Agreements in Indonesian banking practice are generally drafted in the form of standard contracts containing exoneration clauses, which limit or transfer the bank’s legal liability to debtors as consumers. Such clauses may create an imbalance in the legal position of the parties and potentially harm the rights of debtors. In this context, notaries, as public officials authorized to draw up authentic deeds, play an important role in ensuring legal certainty and legal protection for the parties. This study aims to analyze the forms of legal protection available to debtors as bank customers against harmful exoneration clauses in mortgage loan agreements and to examine the responsibility of notaries in drafting credit agreements that contain exoneration clauses. This research employs a normative legal research method using statutory and case approaches. The results of the study indicate that legal protection for debtors against exoneration clauses can be provided through preventive and repressive measures as regulated under Article 18 of Law Number 8 of 1999 concerning Consumer Protection. Furthermore, notaries bear legal responsibility in the preparation of mortgage loan deeds to act honestly, carefully, independently, and impartially in accordance with the Notary Law. Notaries should refuse, explain, or correct exoneration clauses that conflict with prevailing laws in order to ensure fairness, balance, and legal certainty for all parties.